Comparison of functioning and health-related quality of life among patients with HTLV-1, HIV, and HIV-HTLV-1-coinfection - Cleyde Sheyla Chachaqui Marconi; Liliane Lins-Kusterer; Carlos Brites; Mansueto Gomes-Neto (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: Human immunodeficiency virus (HIV) and human T-cell leukemia virus-1 (HTLV-1) viruses are associated with a high global burden of disease, and coinfection is a frequently reported event. We aimed to compare the functioning and health-related quality of life (HRQoL) of patients infected with HTLV-1, HIV, and HIV-HTLV-1. METHODS: We conducted a cross-sectional study of patients older than 18 years who had an HTLV-1 infection (Group A), HIV infection (Group B), or HIV-HTLV-1 coinfection (Group C). The functioning profiles were evaluated using handgrip strength, Berg balance scale (BBS), timed “up and go” (TUG) test, and 5-m walk test (m/s). We used the World Health Organization Disability Assessment Schedule (WHODAS 2.0) questionnaire to measure disability. The HRQoL was evaluated using a 36-item short-form health survey. For data with parametric and non-parametric distribution, we used analysis of variance with Bonferroni correction and the Kruskal-Wallis test, followed by Dunn’s pairwise tests with Bonferroni correction. RESULTS: We enrolled 68 patients in Group A, 39 in Group B, and 29 in Group C. The scores for handgrip strength, BBS, TUG test, all the WHODAS domains, and HRQoL were poorer for Groups A and C than for Group B. CONCLUSIONS: Compared to patients with HIV infection, those with HIV-HTLV-1 coinfection and HTLV-1 infection had poor functioning and HRQoL scores. HTLV-1 infection was associated with reduced functioning and HRQoL in patients with a single HTLV-1 infection and HIV-HTLV-1 coinfection.